Construction and Verification of the Refined Forecast Model for Storm Surges Based on ADCIRC in Guangzhou - LUO Zhifeng; CHEN Gang; DAO Fuhai (Renmin Zhujiang)
Considering the joint influence of upstream water,astronomical tides,and storm surges,this paper constructs a refined forecast model for storm surges in Guangzhou based on ADCIRC.Driven by the Jelesnianski typhoon model,this model takes the upstream water and the forecast of tide levels in the open sea as the upper and lower boundary input and uses the irregularly triangular grids to simulate the topographic change of coastlines.The astronomical tides of six representative tide stations in cities near the Pearl River Estuary are compared with the measured water levels of six tide stations in Guangzhou under the influence of Typhoon Mangkhut and Hato for verification.The results show that the refinement degree of this forecast model can reach the hundred-meter level,and the maximum mean absolute error of astronomical tide fitting is less than 13 cm.The water increasing process,maximum water level value, and occurrence time of storm surges of the two typhoons are well fitted.All of these indicate that the model can basically reflect the astronomical tides and the water increasing process of storm surges along the Pearl River Estuary,which can provide a reference for the warning and high-resolution prediction of storm surges in Guangzhou.